1. 7 + -10 = -3.
2. -3 + -8 = -11
3. 4 + -5 = -1
4. 2 + -6 = -4
(You basically need to add negative numbers to positive numbers in order to get negative numbers.)
Answer:2.31
Step-by-step explanation: considering that the root of 3 has already been given. Will just divide 4 by the root of 3 which is 1.73. and the answer it gives is 2.31
Answer:
x³ - 6x² + 18x - 10
Step-by-step explanation:
(f - g)(x) = f(x) - g(x)
= x³ - 2x² + 12x - 6 - (4x² - 6x + 4)
= x³ - 2x² + 12x - 6 - 4x² + 6x - 4 ← collect like terms
= x³ - 6x² + 18x - 10
29 2 and 1 are the answers